Changing War : the British Army, the Hundred Days Campaign and The Birth of the Royal Air Force, 1918. - Sheffield, Gary (Birmingham war studies series., 2013)
In 1918, the British Expeditionary Force (BEF) played a critical role in defeating the German army and thus winning the First World War. This 'Hundred Days' campaign (August to November 1918) was the greatest series of land victories in British military history. 1918 also saw the creation of the Royal Air Force, the world's first independent air service, from the Royal Flying Corps and the Royal Naval Air Service. Until recently, British histories of the First World War have tended to concentrate on the earlier battles of 1916 and 1917 and often underplayed this vitally important period. Chang.